CULTURE AND SOCIAL MANAGEMENT - Lertgri, Punya; Nillakan, Lunjakon; Saengae Sanjun, Kittiporn; Thaicharoen, Wichian (International Journal of Psychosocial Rehabilitation, 2020)
The culture is an area that determines the characteristics of people who can learn and understand the group of people in that culture because the cultural intensity in each area is different and can be systematically analyzed to understand a group of people more. Establishing a systematic management framework with groups of people when there are social push factors prevents and solves problems affecting people in that culture. The cultural characteristics in each area are different at some level of detail, such as the way of life, values, beliefs, and utensils for transferring and developing to future generations. The management that can access conceptual systems is the process of showing behavior on social occasions or events in advance that will obtain cooperation or gather driving force in various activities to drive as much as needed.